2020
DOI: 10.1080/13662716.2020.1753021
|View full text |Cite
|
Sign up to set email alerts
|

Looking inside the determinants and the effects of entrepreneurial innovation projects in an emerging economy

Abstract: Looking inside the determinants and the effects of entrepreneurial innovations projects in an emerging economy. Industry and Innovation.In press. Looking inside the determinants and the effects of entrepreneurial innovations projects in an emerging economy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 83 publications
(118 reference statements)
0
10
0
1
Order By: Relevance
“…The concepts we focus on and the generic relationships we suggest in this study could be further developed to better adapt to differentiated contexts in which projects are undertaken. Some recent studies highlight bureaucratic and hierarchical organizations, difficulties in accessing financing resources, economic instability and corruption as some features that project managers in emerging economies may have to deal with (Rincon-Gonzalez et al , 2019; Guerrero and Urbano, 2020). Further developments including these specific features would provide a more detailed picture of the interactions between KOS, PM and performance in differentiated contexts.…”
Section: Discussionmentioning
confidence: 99%
“…The concepts we focus on and the generic relationships we suggest in this study could be further developed to better adapt to differentiated contexts in which projects are undertaken. Some recent studies highlight bureaucratic and hierarchical organizations, difficulties in accessing financing resources, economic instability and corruption as some features that project managers in emerging economies may have to deal with (Rincon-Gonzalez et al , 2019; Guerrero and Urbano, 2020). Further developments including these specific features would provide a more detailed picture of the interactions between KOS, PM and performance in differentiated contexts.…”
Section: Discussionmentioning
confidence: 99%
“…In their study Guerrero and Urbano (2021) found that the effects of entrepreneurial innovation improved capabilities in their businesses through the implementation of innovation mixed practices, through innovation in product/services, and through innovation in processes. When businesses developed innovation capabilities in innovation mixed practices of products and processes the probability of developing sustainable entrepreneurial…”
Section: Innovation Theories and Modelsmentioning
confidence: 99%
“…In this study we investigated the level and types of innovations of female social entrepreneurs in Africa (FSEAs) and how they create value in their societies. From the literature it is clear that innovation is an essential entrepreneurial activity (Guerrero & Urbano, 2021;Lumpkin & Frese, 2009;Pearce, Fritz & Davis, 2010;Rauch, Wiklund, Schumpeter & Miller, 1987;Yusoff, Razak, Hassan & Zainol, 2018). Entrepreneurship theories have identified different types (Schumpeter, 1939;Zhao, 2005) and levels (Elbaz, Binkour & Majdouline, 2013;Hamel & Breen, 2007;Lewrick, Williams, Omar & Tjandra, 2015) of innovation.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, longitudinal analyses that quantify the effects of adverse business environments in the national economic development will shed light on the microeconomic role of HGE. Second, the firm’s competitive position will limit the technological and innovative organizational’ strategies (Urbano et al , 2019; Guerrero and Urbano, 2021a, 2021b). Our review suggests that those sectors with a higher rate of knowledge-intensive business/technology entrepreneurs will generate additional competitive pressures to the HGE.…”
Section: Implications and Future Research Agendamentioning
confidence: 99%
“…Although economic growth has been an objective of public policy for a long time, the microeconomic basis has only recently been uncovered to show the high growth firms’ key function (Audretsch, 2012). Particularly, as economies develop, high-growth ventures may provide a missing link to developing economies’ expectations for economic and job creation (Troilo, 2011; Lecuna and Chávez, 2018; Li, 2018; Pawitan et al , 2018; Content et al , 2019; Sá and Pinho, 2019; Urbano et al , 2019; Guerrero and Urbano, 2021a). Besides, Braga et al (2018) suggested that the impact of high-growth businesses on the local economy is dependent on the specific context where those have a place.…”
Section: Introductionmentioning
confidence: 99%